The Role of Mixed Cropping to Climate Change in Sofi District, Harari Regional State, Ethiopia - Hanaa Tharwat, Mohamed Ibrahim; Modiba Maimela, Maxwell; Dekemati, Igor; Simon, Barbara; Muktar, Mohammed; Lisanwork, Negatu (Journal of Central European Green Innovation, 2022)
Az éghajlatváltozás negatív hatásai intenzíven sújtják az afrikai mezőgazdasági ágazatot. Az olyan országok számára, mint Etiópia, amelyek megélhetése elsősorban a csapadékra támaszkodó önellátó mezőgazdaságon alapul, nagyon fontos, hogy alkalmazkodjanak a változó helyzethez. Ezért az éghajlatváltozás negatív hatásainak mérsékléséhez elengedhetetlen a kontextus-specifikus alkalmazkodási stratégiák kidolgozása. A tanulmány célja az volt, hogy azonosítsa azokat a mezőgazdasági gyakorlatokat, amelyek maximalizálják a termelést és kímélik a természeti erőforrásokat. A vizsgálati körzet, a falvak és a reprezentatív válaszadók kiválasztása során háromlépcsős mintavételi eljárást követtek. Ennek megfelelően egy közigazgatási egységet (kebele) és 60 háztartásfőt választottunk ki célzott mintavétellel, illetve szisztematikus véletlenszerű mintavétellel. A talajadatokon és a másodlagos adatokon kívül szerkezetinterjú ütemtervet dolgoztunk ki, előzetesen teszteltük és felhasználtuk a kvantitatív adatok gyűjtésére. A talajelemzés eredménye azt mutatta, hogy az ökológiai mezőgazdaság hozzájárul a talaj kémiai tulajdonságainak javításához, vagyis a vegyes gazdálkodási gyakorlat a talaj pH-értéke, nitrogénje, szervesanyag-tartalma, szerves szén- és elérhető foszfortartalma szignifikánsan eltér a monokultúrás gazdálkodási rendszertől. The negative impact of climate change has been striking the agricultural sector in Africa. For countries like Ethiopia, whose livelihood occupation of the nation is mainly based on subsistence agriculture that highly rely on rainfall, making an adjustment to adapt to the changing situation is very crucial. Therefore, designing contextual specific adaptation strategies are essential to moderate the negative effect of climate change. The aim of the study was to identify the agricultural practices and conserve natural resources. Three stages sampling procedure was followed in selecting the study district, villages and representative respondents. Accordingly, one kebele and 60 household heads were selected using purposive sampling and systematic random sampling, respectively. In addition to the soil data and secondary data, structure interview schedule was developed, pre-tested and used for collecting quantitative data. The soil analysis result showed that organic agriculture contributed for the improvement of soil chemical property that is the mixed cropping farming practice was significantly different in soil pH, nitrogen, organic matter, organic carbon and available phosphorous than in mono cropping farming system. The descriptive result showed that all the farmers (100%) of the sample respondent participated in land preparation and 98.3% of them participated in manure application and also 98.3% of the sample respondents in participated weeding practices. 98.3% of the sample respondents were participated in harvesting activities. 93.3% of the sample respondents were participated in the fertilizer application activities. 68.3% of the sample respondents were participated in irrigation activities. 13.3% sample respondents were participated in seed treatment activates. To adopt organic agriculture practices whereby financial institutions and other agricultural funders should extend credit or support to agricultural activities with farming practices and technologies that promote organic agriculture. This study has shown that organic agriculture can contribute to better soil health and therefore better crop yields thereby strengthening the adaptation efforts of smallholder farmers. It is therefore recommended that smallholder farmers in Sofi district practice organic agriculture farming practices for adaptation efforts.